Tanshinone IIA Suppresses Proliferation and Inflammatory Cytokine Production of Synovial Fibroblasts from Rheumatoid Arthritis Patients Induced by TNF-α and Attenuates the Inflammatory Response in AIA Mice - Du, Hongyan; Wang, Yuechun; Zeng, Yongchang; Huang, Xiaoming; Liu, Dingfei; Ye, Lvlan; Li, Yang; Chen, Xiaochen; Liu, Tiancai; Li, Hongwei; Wu, Jing; Yu, Qinghong; et al. (Frontiers in Pharmacology, 2020)
Rheumatoid arthritis (RA) is a chronic and progressive autoimmune disease, in which activated RA fibroblast-1ike synoviocytes (RA-FLSs) are one of the main responsible for inducing morbidity. Previous reports have shown that RA-FLSs have proliferative features similar to cancer cells, in addition to causing cartilage erosion that eventually causes joint damage. Thus, new therapeutic strategies and drugs, which can effectively contain the abnormal hyperplasia of RA-FLSs and restrain RA development, are necessary for the treatment of RA. Tanshinone IIA (Tan IIA), one of the main phytochemicals isolated from Salvia miltiorrhiza, is capable of promoting RA-FLSs apoptosis and inhibiting arthritis in AIA mice model. In addition, RA patients treated at our clinic with Tan IIA showed significant improvements in their clinical symptoms. However, the detailed molecular mechanism of the Tan IIA effect in RA is unknown. To clarify this mechanism, we evaluated the antiproliferative and inhibitory effects of proinflammatory factors production caused by Tan IIA on RA-FLSs. We demonstrated that Tan IIA can restrict the proliferation, migration and invasion of RA-FLSs in time and dose dependent manner. Moreover, Tan IIA effectively suppressed the increase in mRNA expression of some matrix metalloproteinases and proinflammatory factors induced by TNF-α in RA-FLSs, resulting in inflammatory reactivity inhibition and in blocking the destruction of the knee joint. Trough the integration of the network pharmacology analyzes with the experimental data obtained, it is revealed that effects of Tan IIA on RA can be attributed to its influence on different signaling pathways, including MAPK, AKT/mTOR, HIF-1 and NF-kB. Taken together, these data suggest that the compound Tan IIA has great therapeutic potential for RA treatment.